Comprehensive annotation of the transcriptome of the human fungal pathogen Candida albicans using RNA-seq - Bruno, Vincent M.; Wang, Zhong; Marjani, Sadie L.; Euskirchen, Ghia M.; Martin, Jeffrey; Sherlock, Gavin; Snyder, Michael (Genome Research, 2010)
Candida albicans is the major invasive fungal pathogen of humans, causing diseases ranging from superficial mucosal infections to disseminated, systemic infections that are often lifethreatening. We have used massively parallel high-throughput sequencing of cDNA (RNA-seq) to generate a high-resolution map of the C. albicans transcriptome under several different environmental conditions. We have quantitatively determined all of the regions that are transcribed under these different conditions, and have identified 602 novel transcriptionally active regions (TARs) and numerous novel introns that are not represented in the current genome annotation. Interestingly, the expression of many of these TARs is regulated in a condition-specific manner. This comprehensive transcriptome analysis significantly enhances the current genome annotation of C. albicans, a necessary framework for a complete understanding of the molecular mechanisms of pathogenesis for this important eukaryotic pathogen.
10.1101/gr.109553.110